The effect of preoperative smoking and smoke cessation on wound healing and infection in post‐surgery subjects: A meta‐analysis - Liu, Dazhen; Zhu, Long; Yang, Changhai (International wound journal, 2022)
A meta‐analysis was performed to evaluate the preoperative smoking and smoke cessation on wound healing and infection in post‐surgery subjects. A systematic literature search up to January 2022 incorporated 11 trials involving 218 567 subjects after post‐surgery at the beginning of the study; 176 670 were smoke cessation or non‐smokers, and 41 897 were smokers. Statistical tools like the dichotomous method were used within a random or fixed‐influence model to establish the odds ratio (OR) with 95% confidence intervals (CIs) to evaluate the influence of preoperative smoking and smoke cessation on wound healing and infection in post‐surgery subjects. Smoke cessation or non‐smokers had significantly lower postoperative wound healing problems (OR, 0.59; 95% confidence interval, 0.43‐0.82, P < .001), and surgical site wound infection (OR, 0.74; 95% CI, 0.63‐0.87, P < .001) compared with smokers in post‐surgery subjects. Smoke cessation or non‐smokers had significantly lower postoperative wound healing problems, and surgical site wound infection compared with smokers in post‐surgery subjects. Furthermore, evidence is needed to confirm the outcomes.